In vitro and Ex vivo Analysis of Pitavastatin-Loaded Liposomes for the Treatment of Hyperlipidemia - Delwar, Salma; Islam, Swarnali; Al Mamun, Md Elias; Akter, Nasrin; Dewan, Irin (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Pitavastatin is a BCS class II drug with low solubility and high permeability. So, the purpose of the study was to develop and characterize pitavastatin-loaded liposomes to achieve sustained release of the drug by increasing the solubility as well as bioavailability in treating hyperlipidemia. All formulations were prepared using the ether injection method (EIM) to determine the effect of three independent factors lecithin, cholesterol, and chitosan/PEG-6000 on two dependent variables of percent drug entrapment efficiency (% DEE) and percent cumulative drug release (% CDR) at low (-1) and high (+1) levels, respectively. The prepared liposomes were analyzed using various techniques, including percent DEE, percent CDR, FTIR, S0EM, and zeta potential. After 8 hours of dissolution, the lowest and highest drug releases were 78.01 and 88.70 percent, 68.12 and 80.19 percent, and 66.22 and 78.91 percent, for FCH-4 and FCH-2, FLE-1 and FLE-3, and FPEG-4 and FPEG-3, respectively. Additionally, permeability experiments were conducted by in vitro and ex vivo methods. The particle size of liposomes was between 3.51 μm to 4.19 μm that gave evidence of the formation of uni-lamellar vesicles. The release kinetics were investigated using a variety of mathematical models. SEM and FTIR analyses indicated that liposomes have a spherical and smooth surface with no interaction between medications and excipients. Comparative in vitro and ex vivo studies demonstrated that pitavastatin calcium-loaded liposomes may be viable for patients with hyperlipidemia due to their enhanced solubility and bioavailability. Dhaka Univ. J. Pharm. Sci. 22(1): 43-54, 2023 (June)